Sickle cell trait in French West Indian elite sprint athletes - Marlin, L.; Etienne-Julan, M.; Le Gallais, D.; Hue, O. (International Journal of Sports Medicine, 2005)
The aim of this study was to establish the percentage of sickle cell trait (SCT) carriers among French West Indian sprinters selected for the French National Team in 2000. The investigation determined the number of SCT carriers and the number of national records they had established. Sixteen athletes were indexed (6 males and 10 females). The athletes were within the ranges of 20 - 33 years, 161 - 186 cm and 60 - 80 kg. The results showed the presence of SCT carriers in this population among whom three were SCT carriers (2 males and 1 female) (18.75 %). Moreover, there is a significantly higher percentage of titles and records held by the SCT carriers (38.6 % and 50 %, respectively). In conclusion, this study shows that sickle cell trait carriers are able to perform sprint exercises at the highest levels, and it further indicates that brief and explosive exercise involving mainly the alactic anaerobic metabolism may be enhanced by HbS.